Factorial features of NEET youth socialisation in Kazakhstan in the context of forming a new quality of human capital - Khusainova, Zh.S.; Gazizova, M.R.; Zhartay, Zh.M.; Lambekova, A.N.; Abauova, G.M. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this study is to determine the significance of factors influencing the success of young people's socialisation based on the results of a sociological survey of three focus groups: NEET youth; school, college and university graduates; and government institutions and organisations. Methods: Sociological survey methods for 3 focus groups. Structural equation method and second generation multivariate data analysis (SEM) using Smart PLS 3 software. Findings: The results of structural equation modelling (SEM) based on a sociological survey of three focus groups (NEET youth; school, college and university graduates; state institutions and organisations) revealed the factor specifics of NEET youth socialisation in Kazakhstan – public youth support institutions have a significant impact on the reduction of the NEET segment, state youth policy is a determining factor in the reduction of the NEET segment. Conclusions: As a result of the study, material was obtained, the analysis of which led to the conclusion that the problems of NEET youth, require the active use of institutional and financial mechanisms to support young people, as well as the development of measures to minimise NEET youth in Kazakhstan, as young people are the main source and driving force of socio-economic development of the country.